Bersavine: A Novel Bisbenzylisoquinoline Alkaloidwith Cytotoxic, Antiproliferative and Apoptosis-Inducing Effects on Human Leukemic Cells - Koutova, Darja; Kulhava, Monika; Havelek, Radim; Majorosova, Martina; Královec, Karel; Habartova, Klara; Hošťálková, Anna; Opletal, Lubomír; Cahlikova, Lucie; Řezáčová, Martina (Molecules, 2020)
Bersavine is the new bisbenzylisoquinoline alkaloid isolated from the Berberis vulgaris L.(Berberidaceae) plant. The results of cytotoxicity screening 48 h post-treatment showed thatbersavine considerably inhibits the proliferation and viability of leukemic (Jurkat, MOLT-4), colon(HT-29), cervix (HeLa) and breast (MCF-7) cancer cells with IC50 values ranging from 8.1 to 11 μM.The viability and proliferation of leukemic Jurkat and MOLT-4 cells were decreased after bersavinetreatment in a time- and dose-dependent manner. Bersavine manifested concentration-dependentantiproliferative activity in human lung, breast, ovarian and hepatocellular carcinoma cell linesusing a xCELLigence assay. Significantly higher percentages of MOLT-4 cells exposed to bersavineat 20 μM for 24 h were arrested in the G1 phase of the cell cycle using the flow cytometry method.The higher percentage of apoptotic cells was measured after 24 h of bersavine treatment. Theupregulation of p53 phosphorylated on Ser392 was detected during the progression of MOLT-4 cellapoptosis. Mechanistically, bersavine-induced apoptosis is an effect of increased activity ofcaspases, while reduced proliferation seems dependent on increased Chk1 Ser345 phosphorylationand decreased Rb Ser807/811 phosphorylation in human leukemic cells.
Keywords: HeLa Cells; Hep G2 Cells; apoptóza; buňky Hep G2; Jurkat buňky; Apoptosis; screeningové testy protinádorových léčiv; MFC-7 buňky; fytogenní protinádorové látky; lidé; alkaloidy; HeLa buňky; Cytotoxins; MCF-7 Cells; Antineoplastic Agents, Phytogenic; G1 fáze; cytotoxiny; Alkaloids; leukemie; Leukemia; Drug Screening Assays, Antitumor; Berberis; G1 Phase; HT29 Cells; Jurkat Cells; buňky HT-29; Humans